Coordination-Network-Based Ionic Plastic Crystal for Anhydrous Proton Conductivity - Horike, Satoshi; Umeyama, Daiki; Inukai, Munehiro; Itakura, Tomoya; Kitagawa, Susumu (Journal of the American Chemical Society, 2012)
An ionic coordination network consisting of protonated imidazole and anionic one-dimensional chains of Zn2+ phosphate was synthesized. The compound possesses highly mobile ions in the crystal lattice and behaves as an ionic plastic crystal. The dynamic behavior provides a proton conductivity of 2.6 × 10–4 S cm–1 at 130 °C without humidity.